1996
DOI: 10.1016/s0140-6736(96)03356-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oestrogen during menopause on risk and age at onset of Alzheimer's disease

Abstract: Oestrogen use in postmenopausal women may delay the onset and decrease the risk of Alzheimer's disease. Prospective studies are needed to establish the dose and duration of oestrogen required to provide this benefit and to assess its safety in elderly postmenopausal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
487
2
15

Year Published

1998
1998
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,513 publications
(534 citation statements)
references
References 30 publications
18
487
2
15
Order By: Relevance
“…The hypothesis of a potential role of estrogens in AD has been put forward by a number of epidemiological, retrospective studies that have demonstrated an inverse correlation between estrogen replacement therapy and incidence of AD ( [15,91,117,178,179,228]). These observations have been challenged by a recent randomised clinical trial that showed increased risk of dementia in hormone therapy (HT)-assigned women participating at the Women Health Initiative Study ( [70,193]).…”
Section: Estrogens and Alzheimer's Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…The hypothesis of a potential role of estrogens in AD has been put forward by a number of epidemiological, retrospective studies that have demonstrated an inverse correlation between estrogen replacement therapy and incidence of AD ( [15,91,117,178,179,228]). These observations have been challenged by a recent randomised clinical trial that showed increased risk of dementia in hormone therapy (HT)-assigned women participating at the Women Health Initiative Study ( [70,193]).…”
Section: Estrogens and Alzheimer's Diseasementioning
confidence: 99%
“…Secondary analyses of recent randomized clinical trials, that originally raised controversies among the scientific community as to the risk/benefit ratio of HT ( [85,159,237]), helped to consolidate a novel hypothesis on the efficacy of hormone therapy [200]; it is now hypothesized that HT should be started in early menopause, as a preventative treatment of relatively healthy women, in order to avoid the negative consequences of hypoestrogenicity per se [92]. In fact, observational and randomized clinical trials show that HT does not improve memory or intellectual functions in women already affected by mild to moderate AD ( [70,172,199]), whereas it delays disease onset when administered in healthy perimenopausal women ( [100,117,200,228]). Accordingly, a very recent study demonstrated that surgical menopause is associated with an increased risk of cognitive impairment and dementia in women [195]; novel directions in correctly evaluating specific cognitive functions have also been formulated, since the effect of female steroid hormones on cognitive activities varies across cognitive domains [194].…”
Section: The Timing Hypothesismentioning
confidence: 99%
“…25 , NO . 2 SERMs Modulate NMDA Receptors 243 eases, such as Alzheimer has been recently suggested (Tang et al 1996;Henderson 1997;Inestrosa et al 1998). However, the mechanisms by which these effects of estrogens are yet to be fully characterized.…”
mentioning
confidence: 99%
“…Beneficial effects of estradiol in mood disorders (i.e., depression, pre-menstrual syndrome, post-natal depression), as well as mental diseases, such as schizophrenia and Gille de la Tourette's syndrome, have been reported (Di Paolo 1994;Fink et al 1998). Moreover, a beneficial role of estradiol in neurodegenerative dis-eases, such as Alzheimer has been recently suggested (Tang et al 1996;Henderson 1997;Inestrosa et al 1998). However, the mechanisms by which these effects of estrogens are yet to be fully characterized.…”
mentioning
confidence: 99%
“…Estrogen plays a key role in normal brain functioning and estrogen may have a positive effect on cognition in AD (Fillit, 1994;Henderson et al, 1994). Although the findings of research investigating the effects of HT on AD have been disparate, some studies have reported that females who have used HT are significantly less likely to suffer from AD than females who have never used HT, although HT administered after the diagnosis of AD has not been shown to reverse the pathology (Compton, van Amelsvoort & Murphy, 2001;Tang et al, 1996;Zandi et al, 2002).…”
Section: Introductionmentioning
confidence: 99%